LAGU TURI PUTIH KARYA SUNAN KALIGAJA SEBAGAI INSPIRASI KARYA DENGAN TEKNIK LUKIS TIONGKOK - Zaman, Farid Kurniawan Noor (Jurusan Seni Rupa ISBI Bandung, 2024)
The song Turi Putih is a Javanese song that was written by Sunan Kalijaga, one of the figures who spread Islam in Java. Currently, the popularity of the song Turi Putih has declined and is no longer known, especially among children. In fact, the song has a deep spiritual meaning, especially for Indonesian Muslims. In this research, we will try to visualize the meaning of the song Turi Putih in the form of paintings using Chinese painting techniques. This research has several problem formulations, including: 1) How is the song Turi Putih interpreted? 2) How to visualize the result of Turi Putih song interpretation in Chinese painting? This research method uses qualitative descriptive analysis technique. This research uses a semiotic approach. The production method consists of several steps. The first stage is the search for ideas and ideas. The second stage is the deepening or maturation of ideas. The third or final stage is the realization of the artwork. The production technique is based on Chinese painting techniques. The result of this research is a work that represents the interpretation of the song “Turi Putih” by Sunan Kalijaga. The painting depicts several objects that symbolize death, including white Turi flowers, Kedasih birds, and Besrek batik. Turi putih symbolizes pocong, Kedasih bird is a bird that brings news of death, and Besrek batik is batik used to cover the corpse. The results of this creative research are expected to add insight to readers and contribute to expanding the treasures of global art diversity.